FEATURES OF THE HIGHEST QUALIFICATION IN THE SPECIALTY «INFORMATION AND COMMUNICATION TECHNOLOGIES IN EDUCATION» - O.M. Spirin; A.V. Iatsyshyn (Kherson State University, 2013)
The paper analyzes the prerequisites for developing and becoming of new specialty 13.00.10 - information and communication technology in education. The features of training of the high-qualified specialists at the Institute of information technologies and learning tools of NAPS of Ukraine are examined. The subjects of dissertations on new specialty, are studied the respective research directions in new specialty are defined. The features of the formulation of scientific and categorical apparatus for new specialty are outlined. The experience of training of the high-qualified personnel is discribed.